In Vitro Anti-MRSA and Antioxidants Activities of Different Aerial Part Extracts of Cakile maritima - Shushni M1, Eddeb M1, Mohamed S2, Sufya N2 (AlQalam Journal of Medical and Applied Sciences, 2017)
Background: The increased prevalence of antibiotic resistance, as a result of improper and prolonged antibiotic use, may render the current antimicrobial agents insufficient to control, at least, some bacterial infections. The aerial part of Cakile Maritima was extracted with Soxhlet apparatus using Petroleum ether, DCM and Methanol respectively for 24 hours. The solvents were evaporated under reduced pressure. Methods: To evaluate antimicrobial activity, the agar diffusion assay was used against a Gram-positive bacteria (Staphylococcus aureus, MRSA and Streptococcus pyrogens), three Gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa, and klebsiella peunmonia). Results: Different extracts of Cakile maritima with different concentrations demonstrated an antimicrobial activity against tested pathogenic bacteria. The antioxidant activity of the extracts were tested utilizing DPPH as the radical reagent and ascorbic acid as reference. Conclussion: The methanolic extract showed effective free radical scavening.